Orientation control of regioregular‐poly(3‐dodecylthiophene) films formed by the friction‐transfer method and the performance of organic photovoltaic devices based on these films. Issue 8 (14th November 2013) - Mizokuro, Toshiko; Okamoto, Yukiyasu; Heck, Claire; Aota, Hiroyuki; Tanigaki, Nobutaka
ABSTRACT Control of the molecular orientation of regioregular poly(3‐alkylthiophene)s (RR‐P3ATs) improves the performance of field‐effect transistors and organic photovoltaic devices (OPVs). However, most thiophene ring planes of the RR‐P3AT molecules (except RR‐poly(3‐butylthiophene)) in films formed by the conventional spin‐coating method stand on the substrate, that is, edge‐on orientation. Orientation control of RR‐poly(3‐dodecylthiophene) (RR‐P3DDT) molecules in films formed by the friction transfer method is reported and the performance of OPVs based on friction‐transferred RR‐P3DDT films is compared to that of OPVs based on spin‐coated films. The films are investigated by polarized ultraviolet–visible light absorption spectroscopy, Fourier transform infrared spectroscopy, and grazing‐incidence X‐ray diffraction measurement. For friction‐transferred films, the RR‐P3DDT molecular chain is uniaxially aligned parallel to the substrate plane. In addition, the thiophene ring planes of the RR‐P3DDT molecules are also oriented parallel to the substrate plane, that is, face‐on orientation. The power conversion efficiency (PCE) and fill factor of the RR‐P3DDT/C60 bilayer OPVs based on the friction‐transferred RR‐P3DDT films are higher than those of devices based on spin‐coated films. The PCE and photocurrent of the device based on the friction‐transferred film are larger under irradiation with polarized light parallel to the RR‐P3DDT molecular chain direction than with polarized light orthogonal to the chain direction. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40136.